Evaluation of the Selectivity and Efficiency of Synthetic Sex Pheromones of Leaf-Rollers from Different Manufacturers - Pražanová, Žaneta; Šefrová, Hana (Mendelova univerzita v Brně, 2021)
In 2019 (May-September), the efficiency of pheromone lures for Grapholita funebrana Treitschke, 1835 and Pandemis heparana (Denis & Schiffermüller, 1775) from two manufacturers (Propher, Pherobank) were compared. Monitoring was performed in three study areas in South Moravia (Czech Republic): Kyjov (faunistic square 6968), Brno-Soběšice (6765) and Brno-Starý Lískovec (6865). A total of 14 pheromone traps, from both companies, were suspended. Both target species were found in the traps, with Grapholita funebrana present in all study areas (a total of 5107 adults) and Pandemis heparana was found in Kyjov (64 adults). Furthermore, 2061 individuals of non-target species from the Autostichidae, Noctuidae, Tortricidae and Yponomeutidae families were captured. And 7 non-target species were captured using the pheromone for G. funebrana, most numerously Grapholita molesta (Busck, 1916), Cnephasia stephensiana (Doubleday, 1849) and Argyresthia trifasciata Staudinger, 1871; while, only two non-target species were identified using the pheromone for P. heparana, Noctua fimbriata (Schreber, 1759) and Yponomeuta malinellus Zeller, 1838. Compared to Propher pheromones, Pherobank pheromones were more attractive for target species and less attractive for non-target species.
Keywords: Grapholita funebrana; Non-target species; Pandemis heparana; Pheromone lures; Pheromone traps